2012
DOI: 10.1177/0149206312441834
|View full text |Cite
|
Sign up to set email alerts
|

Choices, Challenges, and Career Consequences of Global Work Experiences

Abstract: Over the past 20 years, there has been increased interest in global forms of employment. Researchers have identified and investigated a number of global work experiences, including corporate and self-initiated expatriates as well as more novel forms of corporate global employees (flexpatriates, short-term assignees, and international business travelers). In this article, the authors review the empirical research that has investigated individual choices, challenges, and career consequences associated with the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
579
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(599 citation statements)
references
References 170 publications
(317 reference statements)
15
579
1
4
Order By: Relevance
“…Nevertheless, the role of capital in developing variables such as job performance and career consequences has been supported by a range of publications (QUIŃONES, Ford, & Teachout, 1995;Shaffer, Kraimer, Chen, & Bolino, 2012).…”
Section: Dimension Developmentmentioning
confidence: 99%
“…Nevertheless, the role of capital in developing variables such as job performance and career consequences has been supported by a range of publications (QUIŃONES, Ford, & Teachout, 1995;Shaffer, Kraimer, Chen, & Bolino, 2012).…”
Section: Dimension Developmentmentioning
confidence: 99%
“…Based on a review of 114 empirical papers published between 1991 and 2011, Shaffer, Kraimer, Chen and Bolino (2012) concluded that the tendency to use exploratory studies in E&R suggests that the field is still in its infancy, with no single dominant methodology. Over 40% of the studies are qualitative, another indication that the field is in the early stages of theoretical development (Shah & Corley, 2006).…”
Section: Research Methods Employed In the Fieldmentioning
confidence: 99%
“…A minority (23%) used mixed methods and only a fraction (7%) employed a longitudinal design. We believe that the methodology ratios identified by Shah and Corley (2006) and by Shortland and Altman (2011) as well as the analysis provided by Shaffer et al (2012) represent the spread of research methodologies employed in the study of E&R in general, with some notable exceptions, such as ethnographic studies (e.g. Lauring & Selmer, 2009) and the use of supplementary secondary data (e.g.…”
Section: Research Methods Employed In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Inability to establish meaningful cross-cultural adaptation and adjustment contributes to the sojourning difficulties which including a decreased in productivity, drop-out among students, premature return, insufficient organizational and social support, intention to leave, learning helplessness and frustration, perceived uneven marginalization and discrimination, strain and stress, turnover or failure, uncertainty in future career development, and unsatisfactory performance (Bhaskar-Shrinivas et al, 2005;Shaffer et al, 2012). In addition, communication breakdown, intercultural conflict and, spouse"s involvement (Lauring and Selmer, 2010) and work-family conflict gives additional strain to the sojourners" international mobility.…”
Section: Cross-cultural Adjustmentmentioning
confidence: 99%